SCHOOL HEAD STRATEGIC MANAGEMENT - Jaya Jaya (International Journal of Southeast Asia, 2020)
The Government has established qualifications and competency standards for education personnel, including Minister of Education Regulation No. 24/2008 concerning school administrative staff competencies, Minister of Education Regulation No.26/2008 concerning laboratories competence, Minister of Education Regulation No. 27/2008 concerning school counselor competencies. School education personnel who have met these standards can be said to be professional education staff. To meet these standards, principals must take special steps, hereinafter referred to as strategic management. This study aims to determine and study the empirical picture of the strategic problems faced by Jambi City 1 High School, Muara Bungo 1 High School and Sungai Penuh City 1 and Sungai Penuh School and the strategy undertaken in responding to the needs of the development of education staff in the future to respond to global competition. This research uses a qualitative method with a descriptive approach, with data collection techniques using interviews, observation and document studies. Data analysis is performed through data display, data reduction and data verification processes. The results of this study are generally the state of professionalism of the teaching staff in Jambi Province State Senior High School not all meet the standards set by the Government. The strategic management of the headmaster of SMA Negeri 1 in Jambi Province begins with a school self-evaluation. The results of the school self-evaluation serve as a reference for the school principal in the formulation of the school's vision, mission and goals as well as the principal's policy in developing professionalism of the teaching staff.